The Effect of HAP addition on the properties F-75 alloy fabricated via P/M for biomaterial applications - Rohaya Abdul Malek (School of Materials Engineering, 2010)
This study has focused on a research on F-75 alloy mixed with HAP fabricated by powder metallurgy (P/M) technique. The objectives of this research are to fabricate composite F-75 with HAP via P/M technique; to identify the optimum weight percentage of HAP to be used in composite fabrication; to study the effect of HAP addition to the microstructures and properties of F-75 alloy for biomaterial applications and to investigate the effect of HAP addition to the corrosion resistance of the composites.